ASHABIYAH THEORY OF IBN KHALDUN: AN ALTERNATIVE PERSPECTIVE FOR STUDYING THE INDONESIAN MUSLIM SOCIETY - UI Ardaninggar Luhtitianti; Achmad Zainal Arifin (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2020)
Ibn Khaldun was popularly known as a Muslim intellectual since the West discovered his work, Muqaddimah. Through this work, he became the only Muslim scientist whose methods and knowledge basis were accepted by the West. Ibn Khaldun became popular with several names, such as Sociologist, Economist, and the founder of social science. However, only few attempts use Ibn Khaldun's perspective as an analytical tool in the discipline of sociology. In Indonesia, the study of the sociology of religion often refers to the big names of sociologists born from the West socio-historical context. Ibn Khladun theory of Al-Umran and Ashabiyah has offered a big concept about civilization, culture, and communal ties that are generated through his research on Muslim society as its focused object. This results of this study reveal that the Ashabiyah theory can be used as an alternative perspective in the study of the sociology of religion, especially to analyze the socio-religious phenomena of the multicultural Muslim society in Indonesia. With the reason that the similarity of the socio-historical context of the object of analysis is very important in determining a perspective to be used. Although, it does not mean that perspectives with different contexts should be abandoned. On the contrary, those perspectives can be used as a complementary perspective, to enrich the scientific treasure in the Sociology of Islam.